PENINGKATAN PEMAHAMAN MATERI PUASA RAMADHAN MELALUI MODEL COOPERATIVE LEARNING TIPE TALKING STICK DI MINU WARU II SIDOARJO - Pratiwi, Sawitri Rahma (Journal Of Islamic Elementary School (JIES), 2019)
Understanding is very important in the process of teaching and learning. The low level of understanding of students in the subjects at MINU Waru II Sodiarjo is caused by a way of teaching teachers who are less creative and monotonous so as to make students bored with learning. The research model used the Classroom Action Research (CAR) model with variables in the form of cooperative learning models of talking stick type and understanding. Based on the results of the study it can be concluded that: (1) Application of the cooperative learning model of the talking stick type can increase the activity of teachers and students. Based on the results of the observation of the teacher's activities, data obtained in the first cycle of 95.58 increased to 96.87 in the second cycle and the results of observations of student activities also increased from the first cycle of 88.23 to 90.62 in the second cycle; (2) There is an increase in the understanding of Fiqh subject matter of Ramadhan fasting in class III students through a cooperative learning model of talking stick type can be shown based on the results of the average score of students' comprehension that in the first cycle obtained an average score of 75.36 and increased to 83 , 5 in cycle II. The number of students who completed in the first cycle was 14 students increased to 20 students in the second cycle, the percentage of completeness of student learning outcomes also increased, the percentage of completeness of student learning outcomes was increased from the first cycle of 63.63% (enough). And in the second cycle of 90.90% (high).